Gaslighting in nursing academia: A new or established covert form of bullying?. Issue 3 (3rd May 2021) - Christensen, Martin; Evans‐Murray, Anne
Abstract: Gaslighting is an insidious, pernicious form of bullying that is gaining notoriety in nursing academia anecdotally. Attempting to identify the behaviors associated with gaslighting are difficult because of the subtle nature with which gaslighting is performed by the perpetrator. Traditional tools/models used for identifying bullying and horizontal violence are not sensitive enough to pick up gaslighting behaviors. Perpetual lies and mistruths, vexatious or frivolous complaints, praise and positive reinforcement, the use of blame or mobbing, and coercion are some of the tactics a gaslighter will use to create confusion and chaos for the gaslightee. The psychological harm for the gaslightee can lead to self‐doubt, hypervigilance, depression, anxiety, addiction, and suicidal ideation as well as the physical symptoms associated with stress. Left with very few choices the gaslightee either adheres to the behavior or leaves. It is important to raise awareness and perhaps education and training of this form of bullying behavior because of the deleterious effects it has personally and professionally.